Evaluation of Different Person-Fit Measures in Cognitive Tests with Different Test Lengths - Marianti, Sukaesi; Manao, Herdin Natalius; Faiha, Arij (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2024)
Test takers’ characteristic is an exciting topic to discuss in psychometric research. In this study, person-fit is a part of the person characteristics applied in the context of cognitive tests. Given the importance of accurately estimating item and person parameters, person-fit is a statistical technique that can detect aberrant responses. Aberrance adversely affects the estimation process at the level of items and persons. The purpose of this study was to introduce and apply two popular person-fit statistics called and . These two statistics were applied in two studies, in study 1 using N = 317 and item = 16, and in study 2 using N = 331 and item = 49. The results showed that in studies 1 and 2,  detected more aberrant responses compared to . Significant differences in estimated results from both techniques were also shown in Study 2. The outcomes of this study are valuable for researchers and practitioners in the field of psychometrics who rely on , as a foundation for identifying aberrant responses.